2009
DOI: 10.1007/s12028-009-9304-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Single-Blinded Comparative Trial of Intravenous Levetiracetam Versus Phenytoin for Seizure Prophylaxis

Abstract: This study of LEV versus PHT for seizure prevention in the NSICU showed improved long-term outcomes of LEV-treated patients vis-à-vis PHT-treated patients. LEV appears to be an alternative to PHT for seizure prophylaxis in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
213
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(222 citation statements)
references
References 28 publications
4
213
3
2
Order By: Relevance
“…Statistically, no significant difference was found between the two drugs in terms of seizure control but the incidence of abnormal EEG was higher in the levetiracetam group in their study (9). A randomized controlled trial by Szaflarski et al compared the two drugs in patients with subarachnoid hemorrhage and traumatic brain injury (17). This study also showed better long-term outcomes in patients that received levetiracetam.…”
Section: █ Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Statistically, no significant difference was found between the two drugs in terms of seizure control but the incidence of abnormal EEG was higher in the levetiracetam group in their study (9). A randomized controlled trial by Szaflarski et al compared the two drugs in patients with subarachnoid hemorrhage and traumatic brain injury (17). This study also showed better long-term outcomes in patients that received levetiracetam.…”
Section: █ Discussionmentioning
confidence: 89%
“…It does not induce fever, cutaneous hypersensitivity reactions or have drug interactions (13). Recently, the effectiveness of levetiracetam has been studied in the prophylaxis of post-traumatic seizures (9) and seizures following trauma and subarachnoid hemorrhage (17). Jones et al (9) have compared the drugs in severe traumatic brain injury and did not find a statistically significant difference between the two drugs.…”
Section: █ Introductionmentioning
confidence: 99%
“…This study is inconclusive as to the effect of levetiracetam. Moreover, a benefit on seizure occurrence after TBI was not observed in a small randomized, single-blinded, comparative trial of levetiracetam versus phenytoin in patients with severe TBI [65].…”
Section: Levetiracetammentioning
confidence: 96%
“…Shorter duration prophylaxis has been advocated and a 3-7 day course of prophylaxis is general practice. Other anti-epileptic agents have been investigated and levetiracetam has been shown to be equally efficacious in reducing early seizures as well as improved functional recovery in comparison to those patients treated with phenytoin [47]. The current recommendation is to consider using short-term (3-7 days) of agents other than phenytoin, such as levetiracetam, for seizure prophylaxis.…”
Section: Seizurementioning
confidence: 99%